Competição territorial por espaços organizacionais em processo de pós-aquisição: um estudo de empresas siderúrgicas brasileiras. - Irineu Dario Staub (2004)
This study aimed at investigating territorial competition for organizational spaces in a postacquisition process between two Brazilian steel industries, based on the discourse of both the acquirer and the acquired companies. It was adopted a qualitative study design with a descriptive-interpretative approach, and a longitudinal perspective. The target population was composed by top and middle level managers, technicians, and other workers who influenced or were affected by the integrative activities. According to the criteria of influence on theprocess, it was selected an intentional sample of individuals, which later became a snowball sample, limited in size by saturation aspects. Primary data were collected through 97 semistructured individual interviews (acquirer, 49; acquired, 48), and participant and nonparticipantobservation. Secondary data were obtained from internal and external sources. Primary and secondary data were analyzed with territorial interaction analysis, combined and complemented by discourse analysis, with focus on territoriality discourses. Results allow foroutlining some implications of using the territorial theoretical perspective for organizational research on acquisitions. The territorial expressions occured into two levels: inter and intraorganizational. At the former, people perceived the acquisition according to their original location in one of the companies, which yielded the core opposition: we versus them that affected all the integrative activities. The process allowed the identification of the steelworkers soul that features the main character of the history, the steelworker. There is no causal linearity linking property and operation, which, as distinct territories, have to be negotiated separately; the former, with the former owners, and the latest, with the workers that dominate the correspondent organizational space. The integration activities depended upon the limits of power and the companies private characteristics. Cultural aspects deeply affected the way people struggled for organizational spaces. At the intraorganizacional level, the territorial competition to take possession of the acquired company was marked by a combination of factors, such as the territorial rationale that yielded the acquisition, the absence of an intervention plan, the occupation game, with the proposition of changes in the acquired companys practices and roles, threats and fears experienced by members of both companies, the defensive maneuvers and the open hostilities towards the members of the acquirer, the manipulation of information manipulation, as territorial defense, the effect of territorial competition on the post-acquisition process, and finally, the integration process that led to the new corporative territory, and finally. The contributions of this case study are: for the organizational theory, the introduction of territoriality as analytical perspective. For the territoriality, the adoption of an approach that explains the personal interactions, at the theoretical level, as an territorial inclusion/exclusion relation; and at the empirical level, as an territorial conquest/defense relation. For the acquisitions studies, the no causal linearity linking property and operation.